Correlating the hydrodynamics of fluidized granular activated carbon (GAC) with membrane-fouling mitigation - Wang, Jingwei (2017)
The mechanical scouring of membranes induced by fluidized particles is a promising method for mitigating membrane fouling. In order to further improve this technique in terms of scouring efficiency and energy requirement, the goal of the current study is to understand the hydrodynamics of the fluidized granular activated carbon (GAC) particles, and correspondingly the relationship between the particle behavioral characteristics and the extent of membrane-fouling mitigation. In this study, the impact of GAC particle diameter (dp), superficial liquid velocity (Ul) and axial position of the membrane (h/H) on particle behavior (namely, particle velocity, concentration and momentum) and membrane fouling was investigated. A high-speed video camera and the ImageJ software were used to characterize particle velocity and concentration, and membrane fouling was characterized by the rate of trans-membrane pressure (TMP) rise. Directly correlating particle behavior with membrane fouling trends shows that higher particle velocities, particle concentration and particle momentum generally all showed a negative correlation with dTMP/dt (i.e., improved fouling control). Of the three characteristics (namely, particle velocity, concentration and momentum), the negative correlation between dTMP/dt and particle momentum was the most pronounced, which suggests that momentum transfer between the GAC particles and the membrane represents a key mechanism effecting the scouring to diminish membrane fouling. Finally, the lack of a strong correlation between dTMP/dt and power input was observed, which indicates that a higher energy expenditure did not guarantee a more effective reduction in membrane fouling.